Utilization of Solar Energy to Enhance Energy Independence in Pematang Serai Village, Langkat Regency - Tharo, Zuraidah; Arnita , Vina; Barus , Dwi Permatasari; Gultom , Jones (CV. Science Tech Group, 2024)
This study aims to evaluate the potential of solar energy in Pematang Serai Village, Tanjung Pura District, Langkat Regency, to support the development of solar power plants (PLTS) as an alternative energy source. This village faces challenges of dependency on fossil energy, which is non-renewable and harmful to the environment. Using qualitative and quantitative research approaches, data collection was conducted through direct observation, interviews, and measurement of sunlight intensity with specialized devices. The results show that the sunlight intensity in this village peaks at 12:00 PM, with an input power of 74.91 W/m² and an average panel efficiency of 15%. The total power produced over six hours reaches 922.38 Wh, providing a significant opportunity to create an energy-independent community through renewable energy utilization. This study suggests the application of PLTS at both household and commercial levels as a practical solution to decrease reliance on fossil energy.